Identifying Dysfunctional Education Ecologies: A DisCrit Analysis of Bias in the Classroom. Issue 2 (3rd April 2018) - Annamma, Subini; Morrison, Deb
Abstract: In this critical theoretical conceptualization situated in Disability Critical Race Theory (Annamma, Connor, & Ferri, 2013), we identify the current education system as a series of dysfunctional education ecologies. We next analyze how dysfunctional education ecologies are maintained through implicit bias, consider how these biases may impact classroom interactions, and reframe bias as dysconscious racism (King, 1991). Finally, we explore how school personnel can use transformative praxis (Freire, 1970) to actively dismantle these dysfunctional education ecologies through a shift in both their epistemological and axiological commitments to develop functional ecologies of learning by enacting a DisCrit Classroom Ecology.